Evaluation of Social Sustainability in Residential Neighborhoods - Mohammadzadeh Neilagh, Zahra; Ghafourian, Mitra (European Journal of Sustainable Development, 2018)
As the consequence of rapid urbanization, in most metropolitan areas, especially in developing countries, due to lack of attachment to the residential neighborhoods, and loss of the inhabitant’s concentration toward their surrounding environment, most of the neighborhoods are gradually eroded both physically and socially. Regarding different aspects of social sustainability and current urban planning standards for residential neighborhoods , it seems that these aspects shall be combined together to produce socially sustainable neighborhoods in every zone of the city and lead to a widely experienced improvement of local identity. In this paper, the selected area included residential neighborhoods in district 12 of Tehran municipality allowing us to study different aspects of social sustainability and survey its indices in a mid-income social class that is relatively uniform and benefit from common services. Keywords: attachment, neighborhood, social sustainability, urbanization.